2000
DOI: 10.1071/ah000152
|View full text |Cite
|
Sign up to set email alerts
|

Emergency medicine and "acute" general practice: comparing apples with 0ranges

Abstract: Emergency Departments (EDs) operate at the interface between the inpatient and ambulatory sectors of health care. Because of shared funding between the Commonwealth and States for ambulatory care, there has been intense focus on the ED patient population, and the potential to shift the locus of care for non-inpatients. One of the frequently cited models for the provision of after-hours GP services is the Balmain General Practice Casualty (GPC). This paper analyses the GPC model, looking in detail at casemix, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 1 publication
0
17
0
2
Order By: Relevance
“…Formal studies to determine the effects of such initiatives are rare, although a recent review found that there was no evidence that they reduced ED demand 21 . The GP casualty model has been clearly disproven as an alternative to properly set up EDs 22 . An analysis by Richardson 23 showed that the introduction of a Canberra nurse walk‐in‐centre led to an increase in patient attendances at the co‐located ED.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Formal studies to determine the effects of such initiatives are rare, although a recent review found that there was no evidence that they reduced ED demand 21 . The GP casualty model has been clearly disproven as an alternative to properly set up EDs 22 . An analysis by Richardson 23 showed that the introduction of a Canberra nurse walk‐in‐centre led to an increase in patient attendances at the co‐located ED.…”
mentioning
confidence: 99%
“…21 The GP casualty model has been clearly disproven as an alternative to properly set up EDs. 22 An analysis by Richardson 23 showed that the introduction of a Canberra nurse walkin-centre led to an increase in patient attendances at the co-located ED. After a year of operation, still no decrease was seen in ED attendances.…”
mentioning
confidence: 99%
“…After-hours general practice clinics have been trialled adjacent to a number of metropolitan emergency departments (Ieraci et al 2000;Ruffin & Hooper 2003;Bolton & Thompson 2001;Liaw et al 2001). There may be a prima facie case for their operation as a means of extending the available hours of access for patients seeking greater flexibility in access to primary care services (Liaw 2001).…”
Section: What Are the Implications?mentioning
confidence: 99%
“…3 Many health services are working to have a general practice clinic in or near public hospitals. Literature on the quantitative effect of general practice clinics is equivocal, [4][5][6][7][8][9][10][11][12][13] particularly in Australia.…”
mentioning
confidence: 99%